Przyjaciel potrzebny od zaraz, czyli o przyjaźni i perswazji w czasopismach dla dzieci - Pomianek-Pudłocka, Agnieszka (Słowo. Studia językoznawcze, 2010)
I analyse the ways the concept friend was understood in Children’s Mags. Chosen texts published in magazines for children are distinguished due to of their target audience — children, that is an unequivalent the lexeme ‘partner’ of a linguistic message. Press definitions of friend show its colloquial meaning, related to culture through the influence of, first of all, family and school. Analysing the ways the lexeme friend is defined I took into consideration the traits used to describe this word. I highlighted the presented depictions with semantic criteria because they all constitute the overall definition of the lexeme. Analyses of the collected materials has let me arrive at the following conclusions. Positive associations outweigh the negative ones in the reception of the friendship-related texts. The meaning of friendship is viewed as an activity in favour of a friend and for their welfare. Proper names, including first names, nick names as well as names of animals are employed to describe friends.